Pengembangan media petualangan cerdas berbasis permainan dengan model ADDIE - Syahfitri, Juwina; Julida Panjaitan, Chery; Anggreni, Fenny (the Study Program of Education for Islamic Elementary School Teachers (Undergraduate), 2023)
This research was conducted at MIS Al-Ashriyah, Langsa City regarding the development of game-based Intelligent Adventure media with the ADDIE model on the theme of ecosystems. The background is the lack of enthusiasm for student learning in class because the learning media used are less varied. The purpose of this study was to determine the development of Intelligent Adventure media with the ADDIE model, the feasibility of the media, teacher responses, and student responses to the media being developed. This type of research is Research and Development (R&D) with the ADDIE development model which consists of five stages, namely Analysis, Design, Development, Implementation, and Evaluation. Data collection techniques in this study were questionnaires. The results of the study show that the feasibility of the media can be seen from the validation results of the three experts. Material expert validation got 86% â€œVery Eligibleâ€. Phase I media validation got 77.5%